Syrian asylum seekers and the question of living in Turkey or returning to their home country: Mardin case - Doğan, Sibel; Tanrıkulu, Faik (Liberte Yayınları, 2020)
Turkey, having faced mass migration since April 2011, has been the country hosting world’s largest population asylum seekers. Within Turkey, the question as to whether Syrians will return to their country has often been the subject of debate. The main objective of the study is to discuss and evaluate the issue of Syrians living in Turkey for short, medium, and long-term periods. This study, via a survey, empirically examines the situation of Syrians from multiple perspectives on their returning tendency. The results of face to face interviews with 284 Syrian asylum seekers in Mardin have been reviewed and according to the results, 56.3% of them are reluctant to leave Turkey. In addition, the Social Adaptation Self-evaluation Scale (SASS), another assessment tool applied in the study, argued that there was no significant relationship between the social adaptations of the asylum seekers and their tendency to return to their home countries (p>0.05). The low, medium, or high levels of social cohesion of asylum seekers do not affect their views on returning. Furthermore, the results of this study indicate that 60.0% of individuals who have spent 5 years and more in Turkey do not plan to return to their home country.

Nisan 2011’den itibaren kitlesel göçlerle karşı karşıya kalan Türkiye dünyanın en fazla mülteci barındıran ülkesi olmuştur. ‘Suriyeliler ülkelerine geri dönecek mi’ sorusu Türkiye’de sıkça tartışma konusu olmaktadır. Türkiye’de yaşayan Suriyelilerin kısa, orta ve uzun vadede ülkelerine dönme veya Türkiye’de kalma ihtimalleri hususunda gerçekçi tespitler yapılması gerekmektedir. Bu araştırma Suriyeli sığınmacıların mevcut durumunu çoklu açılardan ele alarak hem bir durum saptaması hem de “geri dönme eğilimlerini’’ anket ve sosyal uyum modeliyle ortaya çıkarmayı amaçlamaktadır. 284 Suriyeli ile Mardin’de yapılan yüz yüze görüşmelerin sonucuna göre sığınmacıların %56,3’ü Türkiye’den ayrılmak istememektedir. Çalışmada uyguladığımız bir diğer değerlendirme aracımız olan Sosyal Uyum Kendini Değerlendirme ölçeğine göre ise sığınmacıların sosyal uyumları ile ülkelerine geri dönme eğilimi arasında bir ilişki bulunamamıştır (p>0.05). Sığınmacıların sosyal uyum düzeylerinin düşük, orta veya yüksek olması ülkelerine geri dönme düşüncelerini etkilememektedir. Ayrıca bu çalışmada Türkiye’de yaşama süresi 5 yıl ve üstü olan bireylerin %60,0’ının ülkesine dönmeyi düşünmediğini ortaya çıkarmıştır.
Mardin örneğinde Suriyeli sığınmacılar: Türkiye’de kalmak ya da geri dönmek
Keywords: Asylum-Seekers; Returns; Syrian Civil War; Migration; Syrians; Sığınmacılar; Geri Dönüş; Suriye İç Savaşı; Göç; Türkiye’deki Suriyeliler